2016
DOI: 10.5114/wo.2016.64600
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of Caphosol in prevention and alleviation of acute side effects in patients treated with radiotherapy for head and neck cancers

Abstract: Aim of the studyOral mucositis is a common side effect of the oral mucosa due to anticancer therapy, especially for head and neck cancer. Caphosol is indicated for dryness of the mouth and oropharynx and treatment of mucositis due to irradiation or high-dose chemotherapy. The aim of the study was to evaluate the efficacy of Caphosol in preventing and alleviating mucositis due to radiotherapy in the head and neck region.Material and methodsCaphosol was used from the beginning of the irradiation and for two week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…A search for recently published articles about SCPR identified a large RCT, which concluded that SCPR was ineffective in the management of OM in H&N cancer patients treated with RT/RT-CT [83]. A recent RCT in pediatric patients [84] and comparative studies about SCPR indicated conflicting results about the effectiveness in preventing OM [23,85].…”
Section: Discussionmentioning
confidence: 99%
“…A search for recently published articles about SCPR identified a large RCT, which concluded that SCPR was ineffective in the management of OM in H&N cancer patients treated with RT/RT-CT [83]. A recent RCT in pediatric patients [84] and comparative studies about SCPR indicated conflicting results about the effectiveness in preventing OM [23,85].…”
Section: Discussionmentioning
confidence: 99%
“…were also reported in the adult population with head and neck cancer undergoing radiotherapy or radiochemotherapy. 20 A few randomized trials Note. Model was fitted using R-package nlme's lme( ) function.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have shown positive effects of Caphosol in the frequency, intensity, and duration of overt OM in adult patients undergoing chemotherapy treatment and SCT 17‐19 . Favorable results were also reported in the adult population with head and neck cancer undergoing radiotherapy or radiochemotherapy 20 . A few randomized trials 13,21,22 have studied Caphosol in the context of mucositis prevention in adults and have reported no benefit.…”
Section: Discussionmentioning
confidence: 99%
“…In an additional study not included in this review, patients receiving radiation to the head and neck received prophylactic Caphosol. 7 Dosing was initiated four times daily and could be increased up to 10 times daily depending on symptoms. In this study, there was a statistically significant decrease in mucositis level, dysphagia, xerostomia, opioid analgesia requirements, and frequency of prolonged hospitalizations.…”
Section: Discussionmentioning
confidence: 99%